Humor Discourse in Art Performances of Shadow Puppets Cenk Blonk - Gede Wira Ady Saputra; Aron Meko Mbete; I Nyoman Muliana (CV Wahana Publikasi, 2022)
Humor discourse as non-bonafide discourse is frequently found daily. The existence of humor, besides for entertainment purposes, is also being used for educational purposes, also culture and language conservation. Some approaches can be implied to understand how discourse humor is created. One of them is through language elements and pragmatism flouting. This research of humor discourse in art performances of shadow puppets aims to analyze the utilization of language elements and pragmatism flouting. This study uses a mixed-method approach. The data of this research are in the form of conversation found in the dialogue of shadow puppets performances. As the results, it was found that humor discourse is formed by the first utilization of language elements such as phonological utilization (5.56%), lexical ambiguity (3.70%), grammatical ambiguity (31.48%), rhyme utilization, and language style (59.26%); secondly, Maxim flouting such as quantity flouting (39.13%), quality flouting (21.74%), manner flouting (17.39%), relevance flouting (21.74%).